Quality of life among post-menopause women in Kubang Kerian, Kelantan - Shazuki, Nur Syafiqah Anuar (2020)
Menopause is a condition in which a woman stops menstruation permanently and is unable to conceive again. Menopause involves changes in the iological, physiological anf physical aspects that afect the health and well-being of the women. The purpose of this study is to determine the quality of life of post-menopause women in Kubang Kerian, Kelantan. A cross-sectional study was conducted involving 40 participants through random probability selection method. Structured and self-administered questionaire were used for data collection purposes from February 2020 to March 2020. Independent T-test were used to determine the relationship beteen socio-demographic characteristics and the quality of life among the women. The results showed that 95% of the participants had good quality of life. Statisticss show a significant relationship between duration of menopause and quality of life p = 0.037 (p <0.05). The results of this study can be concluded that vasomotor domain is the most domain that highly afected the quality of life where statistics shows that p = 0.001 (p <0.05). This study shows that in it important to now the quality of life among post-menopause women so that their quality of life is at an optimal level.